Regional development perspectives of Slovenia - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The regional development perspective of Slovenia is discussed within the specific regional structure, strategy of balanced regional development and problems of population, settlement, economic and spatial disparities between twelve statistical regions.
Keywords: naselja; prebivalstvo; regionalni razvoj; regionalno gospodarstvo; regionalno planiranje; Slovenia; Slovenija